Influence of culture change on the perception of fear and anxiety pathways in Endodontics: A pilot proof of concept study. (16th January 2018) - Carter, Ava Elizabeth; AlShwaimi, Emad; Boschen, Mark; Carter, Geoffery; George, Roy
Abstract: This study assessed the influence of cultural changes (known as acculturation) on pathways of fear and anxiety in Endodontics. A purposive sampling technique identified patients of Saudi Arabian descent living in Australia and Saudi Arabia. Only patients with root canal fillings (or treatment planned for endodontic treatment) were included. Patients with intellectual disabilities, surgical root therapy, and aged under 20 were excluded. Consenting patients attending the dental clinics of University of Griffith University, Australia and University of Dammam, Saudi Arabia completed the "My Endodontic Fear Questionnaire." Three hundred and twenty‐four patients (21–75 years) were included, 90% of participants reported more than one pathway. Australian Saudi Arabians mainly utilised vicarious pathway (94.9%), whilst Saudi Arabians utilised the verbal threat (93.5%) and parental pathway (78.3%). This study highlights the possible role of acculturation on the perception of fear and anxiety in Endodontics; however, further research with other ethnic groups is essential to enhance our understanding.